Hair growth promoting activity of Carthamus tinctorius florets extract-loaded nanostructured lipid carriers - Naphatsorn Kumar (2018)
© 2015, International Journal of Pharmacy and Pharmaceutical Sciences. All rights reserved. Objectives: This work was aimed to formulate, characterize and determine hair growth promoting activity of the Carthamus tinctorius (safflower) florets extract-loaded nano structured lipid carriers (NLC) in C57BL/6 mice. Methods: Safflower florets were extracted by maceration with ethanol, and then incorporated into NLC formula. Safflower extract-loaded NLCs were assessed for their physical properties, stabilities and hair growth promoting activity in C57BL/6 mice. Results: Safflower-loaded NLCs had particle size around 100 nm, zeta potential in the range of -40 to -49 mV. The data from DSC and XRD suggested that this NLC occurred as an amorphous type NLC. Safflower extract-loaded NLC promoted hair growth in the mice better than minoxidil. Safflower yellow, the principle phytochemical in safflower extract, along with synergistic activity between other phytochemicals may account for hair growth promoting activity observed in mice. The further investigations in human volunteer should be conducted for the confirmation. Conclusion: Safflower-loaded NLC that provided good physical properties and stabilities, exerted hair growth promoting activity in C57BL/6 mice.